Dynamic quenching as a simple test for the mechanism of excited-state reaction - (:unkn) unknown (ELSEVIER, 2007)
We report on comparative studies of dynamic fluorescence quenching of 3-hydroxyflavone (3HF) and of its novel analogs by nitric oxide spin compound TEMPO. These dyes exhibit the excited-state intramolecular proton transfer (ESIPT) reaction that allows observation of two separate bands in fluorescence emission - of initially excited form and of the product of ESIPT reaction. In the frame of two-state excited-state reaction formalism, we develop the theory predicting different dependence of intensities at two bands in steady-state spectra in the cases of thermodynamic and kinetic control of ESIPT. In line with these predictions, the quenching changes strongly the distribution of intensities between these bands for 3HF but does not change it for the novel compounds whose excited states exhibit strong charge transfer character. Based on these findings, we suggest that the quenching of fluorescence by an efficient collisional quencher can be a simple and convenient method using only the steady-state experiment for distinguishing the excited-state reactions occurring under thermodynamic or under kinetic controls. This method can be used for large-scale screening of a series of compounds potential candidates for application in fluorescence sensor and biosensor technologies. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: fluorescence sensors and probes; collisional quenchers; excited-state reactions; kinetic and thermodynamic control; 3-hydroxyflavone; excited-state intramolecular proton transfer; PROTON-TRANSFER SPECTROSCOPY; 2-COLOR FLUORESCENCE PROBE; INTERMOLECULAR INTERACTIONS; TRANSFER KINETICS; 3-HYDROXYFLAVONE; 3-HYDROXYCHROMONE; PERTURBATION; RESOLUTION; DECAY